PENGATURAN SUMBER DAYA ALAM DI LANDAS KONTINEN SEHUBUNGAN DENGAN BERLAKUNYA KONVENSI HUKUM LAUT PBB 1982 KHUSUSNYA BAGI INDONESIA - Munsharif Abdul Chalim (Unissula, 2011)
Continental shelf is a relatively new concept in international law of the sea. Full authority and exclusive rights over natural resources located in the continental shelf region and its ownership is on the coastal state, where the meaning of this natural wealth is a source of minerals and other lifeless on the seabed and subsoil. Through the establishment of the United Nations Convention on the Law of the Sea 1982, as well as enactment of the provisions of the New Law of the Sea, Indonesia is an archipelagic state which is seen as a unified whole between the islands and waters. We realized the sea was rich in minerals mining goods that is priceless natural resources, which is expected to be able to fulfill the needs of the world if mineral resources on land are not sufficient or run out completely. In Indonesia, mostly consisting of ocean territory, surely have the very wide continental shelf, where there is a variety of natural resources, especially oil and gas resources. Hence it needs regulation for the natural resources utilization in the region.Keywords :Â Continental Shelf, Natural Resources, Seabed and Subsoil.